TLR2 Promoter Hypermethylation Creates Innate Immune Dysbiosis. (January 2015) - Benakanakere, M.; Abdolhosseini, M.; Hosur, K.; Finoti, L.S.; Kinane, D.F.
Periodontitis is a common chronic inflammatory disease that is initiated by a complex microbial biofilm that poses significant health and financial burdens globally. Porphyromonas gingivalis is a predominant pathogen that maintains chronic inflammatory periodontitis. Toll-like receptors (TLRs) play an important role in periodontitis by recognizing pathogens and maintaining tissue homeostasis. Deficiencies in TLR expression and downstream signaling may reduce the host's innate defenses against pathogens, leading to bacterial persistence and exacerbated inflammation, which are now being better appreciated in disease pathologies. In the case of periodontitis, gingival epithelial cells form the first line of defense against pathogens. Innate immune dysregulation in these cells relates to severe disease pathology. We recently identified a blunted TLR2 expression in certain gingival epithelial cells expressing diminished cytokine signaling upon P. gingivalis stimulation. Upon detailed analysis of the TLR2 promoter CpG Island, we noted higher CpG methylation in this dysregulated cell type. When these cells were treated with DNA methyltransferase inhibitor, TLR2 mRNA and cytokine expression were significantly increased. If TLR2 expression plasmid was ectopically expressed in dysfunctional cells prior to P. gingivalis stimulation, the cytokine expression was increased, confirming the requirement of TLR2 in the P. gingivalis– mediated inflammatory response. We designed a chronic in vitro infection model to test if P. gingivalis can induce DNA methylation in normal gingival epithelial cells that express higher TLR2 upon agonist stimulation. Chronic treatment of normal epithelial cells with P. gingivalis introduced de novo DNA methylation within the cells. In addition, increased DNA methylation was observed in the gingiva of mice infected with P. gingivalis in a periodontitis oral gavage model. Moreover, tissues obtained from periodontitis patients also exhibited differential TLR2 promoter methylation, as revealed by bisulfite DNA sequencing. Taken together, DNA methylation of TLR2 can modulate host innate defense mechanisms that may confer increased disease susceptibility.